Age, Race/Ethnicity, and Offense Severity: An Examination of the Liberation Hypothesis for Juvenile Case Outcomes at Final Disposition - Bryson, Sara (Crime & delinquency, 2025)
Prior research on juvenile court processing indicates that legal and extralegal factors impact outcomes at judicial disposition. Less is known, however, if the combined effects of certain characteristics influence decision-making. Applying the liberation hypothesis, this study investigates the interactive effects of a juvenile’s age, race/ethnicity, and offense severity on dispositional outcomes. Using all adjudicated complaints from North Carolina between 2011 and 2018, results suggest that irrespective of a juvenile’s age, youth of color had greater odds of receiving residential placement than community-based sanctions. Regardless of offense severity, Black youth were treated more punitively than Hispanics and Whites. Findings underscore the importance of acknowledging disparities in case outcomes and creating programming options within juvenile justice to meet the needs of youth of color.